(untitled) (The International Journal for Scientific Research, 2024)
This research study seeks to establish the topic of “The Prophetic Method in Building Human Individual Responsibility in Islam as a Model,” after the role of individual responsibility was absent from the reality of Muslims for many centuries, in order to reach an awareness of individual responsibility in the Sunnah of the Prophet, to resolve the answer to the question: What is the Prophetic Method? In building the individual responsibility of man in Islam? This study has followed the inductive, descriptive and analytical approach based on depicting the issues and then analyzing and establishing them legally according to the approved research methods.